2016
DOI: 10.3892/mmr.2016.5508
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of kif3a results in defective osteoblastic differentiation in dental mesenchymal stem/precursor cells via the Wnt signaling pathway

Abstract: The anterograde intraflagellar transport motor protein, kif3a, regulates the integrity of primary cilia and various cellular functions, however, the role of kif3a in dental mesenchymal stem/precursor cell differentiation remains to be fully elucidated. In the present study, the expression of kif3a was knocked down in human dental follicle cells (hDFCs) and human dental pulp cells (hDPCs) using short hairpin RNA. The results of subsequent immunofluorescence revealed that knocking down kif3a resulted in the loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…KIF3A was also reported to be associated with certain pathological processes. It has been reported that KIF3A is involved in forming defective bone formation and osteopenia ( 13 ) and defective osteoblastic differentiation in dental mesenchymal stem/precursor cells ( 14 ). Since 2013, the expression and function of KIF3A has been regarded as statistically significantly and correlated with several tumors such as glioblastoma, prostate cancer and medulloblastoma ( 4 , 5 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…KIF3A was also reported to be associated with certain pathological processes. It has been reported that KIF3A is involved in forming defective bone formation and osteopenia ( 13 ) and defective osteoblastic differentiation in dental mesenchymal stem/precursor cells ( 14 ). Since 2013, the expression and function of KIF3A has been regarded as statistically significantly and correlated with several tumors such as glioblastoma, prostate cancer and medulloblastoma ( 4 , 5 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because many central cilia genes, such as Aurka, the aurora kinase A gene, are also directly implicated in proliferation (Fu et al, 2007), we had to identify a candidate that was, rather, involved in cilia organization. We selected Kif3a, encoding the kinesin family member 3A, which has been documented as a key factor in ciliogenesis and the intraflagellar transport of primary cilia (Jiang et al, 2016;Rosenbaum and Witman, 2002). Murine Kif3a expression was significantly less in NZO, as compared with B6-ob/ob, islets ( Figure 6A, left), and KIF3A protein tended to be decreased after high glucose treatment ( Figure 6A, right).…”
Section: Kif3a Suppression In Min6 Beta Cells and Primary Mouse Isletmentioning
confidence: 99%
“…It is usually known that the Wnt/b-catenin pathway plays an important role in homeostasis and osteogenesis [54,55]. Jiang S et al [56] reported that SHEDs could differentiate into osteoblasts and odontoblasts and suppress the adipogenic differentiation through Wnt signaling pathways. Results from Western blot were in agreement with the results from qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%